Ten-year mixed-method evaluation of prelicensure health professional student self-reported learning in an interfaculty pain curriculum. (14th September 2022) - Dale, Craig M.; Cioffi, Iacopo; Murphy, Laura; Langlois, Sylvia; Musa, Renata; Stevens, Bonnie
Abstract : Students attending learning sessions at the University of Toronto Interfaculty Pain Curriculum (2009–2019) in Toronto, Canada, self-report high ratings of knowledge acquisition and effective presentation methods. Abstract : See commentary: Trouvin A-P. "Ten-year mixed method evaluation of prelicensure health professional student self-reported learning in an interfaculty pain curriculum": a view on pain education. PAIN Rep 2022;7:e1031. Abstract: Introduction: Student perspectives on interprofessional pain education are lacking. Objectives: The purpose of this study was to evaluate ratings of knowledge acquisition and effective presentation methods for prelicensure health professional students attending the University of Toronto Centre for the Study of Pain Interfaculty Pain Curriculum (Canada). Methods: A 10-year (2009–2019) retrospective longitudinal mixed-methods approach comprising analysis and integration of quantitative and qualitative data sets was used to evaluate 5 core University of Toronto Centre for the Study of Pain Interfaculty Pain Curriculum learning sessions. Results: A total of 10, 693 students were enrolled (2009–2019) with a mean annual attendance of 972 students (±SD:102). The mean proportion of students rating "agree/strongly agree" for knowledge acquisition and effective presentation methods across sessions was 79.3% (±SD:3.4) and 76.7% (±SD:6.0), respectively. Knowledge acquisition or presentation effectiveness scores increased, respectively, over time for 4 core sessions: online self-study pain mechanisms module ( P = 0.03/ P < 0.001), online self-study opioids module ( P = 0.04/ P = 0.019), individually selected in-person topical pain sessions ( P = 0.03/ P < 0.001), and in-person patient or interprofessional panel session ( P = 0.03). Qualitative data corroborated rating scores and expanded insight into student expectations for knowledge acquisition to inform real-world clinical practice and interprofessional collaboration; presentation effectiveness corresponded with smaller session size, individually selected sessions, case-based scenarios, embedded knowledge appraisal, and opportunities to meaningfully interact with presenters and peers. Conclusion: This study demonstrated positive and increasing prelicensure student ratings of knowledge acquisition and effective presentation methods across multifaceted learning sessions in an interfaculty pain curriculum. This study has implications for pain curriculum design aimed at promoting students' collaborative, patient-centered working skills.